Staged electrochemical treatment guided by modelling allows for targeted recovery of metals and rare earth elements from acid mine drainage. (1st December 2020) - Brewster, Emma Thompson; Freguia, Stefano; Edraki, Mansour; Berry, Luke; Ledezma, Pablo
Abstract: Acid mine drainage (AMD) is a challenge for current and legacy mining operations worldwide given its potential to severely harm ecosystems and communities if inadequately managed. Treatment costs for AMD are amongst the highest in the industrial wastewater treatment sector, with limited sustainable options available to date. This work demonstrates a novel chemical-free approach to tackle AMD, whereby staged electrochemical neutralisation is employed to treat AMD and concomitantly recover metals as precipitates. This approach was guided by physico-chemical modelling and tested on real AMD from two different legacy mine sites in Australia, and compared against conventional chemical-dosing-based techniques using hydrated lime (Ca(OH)2 ) and sodium hydroxide (NaOH). The electrochemical treatment demonstrated the same capacity than Ca(OH)2 to neutralise AMD and remove sulfates, and both were significantly better than NaOH. However, the electrochemical approach produced less voluminous and more easily settleable sludge than Ca(OH)2 . Moreover, the staged treatment approach demonstrated the potential to produce metal-rich powdered solids with a targeted composition, including rare earth elements and yttrium (REY). REY were recovered in concentrations up to 0.1% of the total solids composition, illustrating a new avenue for AMD remediation coupled with the recovery of critical metals. Graphical abstract: Image 1 Highlights: Novel staged electrochemical treatment removes all metals from acid mine drainage. System behaviour and removal dynamics can be predicted by physicochemical modelling. Demonstration of acid mine drainage neutralisation without chemical dosing. Treatment concomitantly recovers valuable metals of interest at competitive OPEX. Novel treatment opens the opportunity to design 'tailored' metal-rich precipitates.